Patients’ Satisfaction with Primary Health Care in Egypt: Exploring the Gap between Rural and Urban Governorates - Metwally, Dina (Journal of Social and Development Sciences, 2014)
Patient satisfaction has been frequently used as an indication of the overall quality of health care providers. Understanding patients` needs and expectations is crucial to PHC providers to improve patients` health. This study aims to explore patients’ satisfaction with primary health care services in urban and rural areas in Egypt. The study shows a gap in patient`s satisfaction across Alexandria and Sohag governorates. This implies a difference in reform implementation across urban and rural governorates. More attention should be given to different dimensions of health care provision at PHC level in rural governorates including clinical and nonclinical training of nurses, improvement in amenities and other facilities, improvement of registration system, and promoting the new system.